The Effects of a Comprehensive Psychosocial Intervention on Secondary Stressors and Social Support for Adult Child Caregivers of Persons With Dementia. Issue 2 (22nd June 2018) - Gaugler, Joseph E; Reese, Mark; Mittelman, Mary S
Abstract: Background and Objectives: Many evaluations of nonpharmacologic interventions for family members of persons with Alzheimer's disease or related dementias (ADRDs) exist, but few consider effects on outcomes that are pertinent to caregivers' roles and relationships. The current study evaluated the efficacy of the New York University Caregiver Intervention-Adult Child (NYUCI-AC) on perceptions of family conflict, role conflict (effects of family caregiving and time, family, and social life), and perceived social support for adult child caregivers of relatives with ADRD over a 3-year period. Research Design and Methods: A single-blinded randomized controlled trial design was used. One-hundred and seven adult child caregivers were enrolled in the NYUCI-AC and randomly assigned to a treatment or contact control group. Assessments were scheduled to be completed every 4 months during the first year of participation and every 6 months thereafter for up to 3 years. Individual growth curve models were utilized to ascertain the effects of the NYUCI-AC on change in family conflict, role conflict, and perceptions of social support. Results: Among the entire sample, role conflict significantly ( p < .05) declined and satisfaction with instrumental assistance increased over the course of the study, whereas family conflict slightly increased over the initial study period and then declined slightly. The findings indicated that the NYUCI-AC did not exert statistically significant effects on changes in family conflict, role conflict, or perceptions of social support over the 3-year study period. Discussion and Implications: Although the clinical content of some dementia caregiver interventions is tailored to the specific needs of each caregiver and family, the outcomes selected to judge the efficacy of these interventions might not follow similar principles. Incorporating clinical content and evaluation outcomes that are family-centered will help to advance the state of the art of dementia caregiving interventions.